Analisis Pola Asuh Ibu Yang Bekerja Terhadap Sosial Emosional Anak Usia Dini Di PAUD Mutiara Hati - Erna Nunafisa; Muthia Sari; Vina Karina Putri (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Early Childhood Education (ECE) is a crucial foundation for children’s social and emotional development, which is strongly influenced by parenting practices, particularly those of mothers. However, the increasing number of working mothers presents challenges that may affect children’s developmental outcomes. This study aims to analyze the parenting patterns of working mothers and identify the inhibiting factors that influence the social-emotional development of young children at PAUD Mutiara Hati. This research employed a qualitative method with a descriptive approach. The primary informants consisted of five working mothers selected through purposive sampling, supported by five teachers as secondary informants. Data were collected through in depth interviews and naturalistic observations. The findings indicate that the dominant parenting style applied by working mothers is the authoritative or democratic style, characterized by warmth, two way communication, and consistent guidance despite limited time. Some mothers also adopted situational approaches, such as authoritarian or responsive parenting, depending on the child’s condition. Furthermore, several inhibiting factors were identified, including limited time availability, physical and emotional fatigue, job demands, lack of social support, and economic pressures. In conclusion, working mothers can still provide effective parenting as long as they receive adequate environmental support, maintain work flexibility, and sustain consistent interactions with their children